Предмет: Алгебра,
автор: olgakostyukova1
Упростить1) (7а-9b)+(3b+2a)
mikhailgredski:
Вообще=то (7a-9b) + (3b + 2a) = 7a - 9b + 3b + 2a = 9a - 6b = 3 * (3a -2b)
Ответы
Автор ответа:
0
(7a-9b)+(3b+2a)=7a-9b+3b+2a=9a-6b
Вроде бы так!!!
Автор ответа:
1
(7а-9ь)+(3ь+2а)=7а-9ь+3ь+2а=9а-6ь
Похожие вопросы
Предмет: Английский язык,
автор: Аноним
Предмет: Химия,
автор: MazikinMaze
Предмет: Алгебра,
автор: amirbaiguanyshev03
Предмет: Математика,
автор: артёмка0071000000
Предмет: Математика,
автор: nastya50389